Morphological and Physiological Responses of Enhalus acoroides Seedlings Under Varying Temperature and Nutrient Treatment - Artika, Suci Rahmadani; Ambo-Rappe, Rohani; Teichberg, Mirta; Moreira-Saporiti, Agustín; Viana, Inés G. (Frontiers in Marine Science, 2020)
Seagrass meadows are declining globally. In Indonesia, 75% loss has been reported in the last 5 years. The decrease of the seagrass area is influenced by the simultaneous occurrence of many factors at the local and global scale, including nutrient enrichment and climate change. This study aims to find out how increasing temperature and nutrient enrichment affect the morphological, biochemical and physiological responses of Enhalus acoroides in the seedling phase, which has not previously been studied. To achieve these aims, a laboratory experiment of combined temperature and nutrient treatments was conducted using recently-germinated seedlings of E. acoroides. The results showed that the seedlings were tolerant to an extended exposure to the current ambient maximum temperature. Under higher temperature treatment, the seedlings were observed to increase in aboveground size traits (e.g., number of leaves, leaf length, biomass and leaf area), as well as in belowground traits, such as root length. The results in this study also showed that the initial seed size matters for morphological responses. On the contrary, nutrient responses of seedlings were practically absent, suggesting they could rely on internal reserves. Interaction between both factors was limited, with the exception of low temperature and high nutrient treatment, in which the AG:BG ratio and leaf elongation rate increased. Fluorescence parameters were not influenced by any of the water treatments. The results in this study suggest that E. acoroides seedlings rely energetically in the reserves within the seedling and that increasing temperature might result in faster seedling development, although no interactions with other organisms were tested. This is of importance when studying the resilience capacity of this species and when restoration attempts are planned, as a faster root development would provide a faster stabilization in the sediment and the survival of the whole plant.